2003
DOI: 10.4315/0362-028x-66.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Poliovirus 1, Bacteriophages, Salmonella Montevideo, and Escherichia coli O157:H7 on Strawberries by Physical and Disinfectant Washes,

Abstract: The efficacy levels of different physical and chemical washing treatments in the reduction of viral and bacterial pathogens from inoculated strawberries were evaluated. Escherichia coli O157:H7, Salmonella Montevideo, poliovirus 1, and the bacteriophages PRD1, phiX174, and MS2 were used as model and surrogate organisms. Chemicals readily available to producers and/or consumers were evaluated as antimicrobial additives for the production of washes. The gentle agitation of contaminated strawberries in water for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…Washing raspberries and strawberries was shown to result in approximately 1 log 10 cfu/g reduction in a mixture of five serovars of Salmonella enterica (Agona, Baildon, Gaminara, Michigan, and Montevideo) (Bialka and Demirci, 2007b). Similar results from washing alone were reported by Lukasik et al (2003) for Salmonella enterica serovar Montevideo inoculated onto strawberries. A slight increase in the effect of washing on reducing Salmonella contamination of strawberries was reported after the addition of sanitizing agents into the washing process (Raiden et al, 2003).…”
Section: Description Of Processing Methods For Berriessupporting
confidence: 74%
See 1 more Smart Citation
“…Washing raspberries and strawberries was shown to result in approximately 1 log 10 cfu/g reduction in a mixture of five serovars of Salmonella enterica (Agona, Baildon, Gaminara, Michigan, and Montevideo) (Bialka and Demirci, 2007b). Similar results from washing alone were reported by Lukasik et al (2003) for Salmonella enterica serovar Montevideo inoculated onto strawberries. A slight increase in the effect of washing on reducing Salmonella contamination of strawberries was reported after the addition of sanitizing agents into the washing process (Raiden et al, 2003).…”
Section: Description Of Processing Methods For Berriessupporting
confidence: 74%
“…The different experimental set up of these studies also makes the comparison between different studies difficult. Lukasik et al (2003) reported the effect of different treatments against Salmonella enterica serovar Montevideo at 10 7 /ml inoculated onto strawberries. Reductions of almost 2 log units (>98 %) in numbers of Salmonella were obtained with sodium hypochlorite (50 to 300 ppm of free chlorine), "stabilized chlorine dioxide" (200 ppm), peroxyacetic acid (100 ppm), and acidified sodium chlorite (100 or 200 ppm) (Lukasik et al, 2003).…”
Section: Specific Mitigation Options To Reduce the Risk Of Salmonellamentioning
confidence: 99%
“…Application of the bactericidal effect of ASC for surface washing of raw salmon 52 , beef carcass 11 , and broiler carcasses 26 has been studied. However, only a few studies have been performed to apply the bactericidal effect of ASC for the surface washing of raw vegetables or fruits 18,34 . We constructed a sensitive detection system for injured bacteria 20 and evaluated the effectiveness of ASC in killing E. coli O157:H7 on leafy vegetables with a view to its potential application to foods and food contact surfaces as an anti-microbial treatment 22 .…”
Section: Sanitation Of the Attached Bacteria On The Surface Of Raw Vementioning
confidence: 99%
“…Its antimicrobial effectiveness has been demonstrated in bacteria, including the pathogenic Escherichia coli O157:H7 (Kim and Slavik 1994), Salmonella typhimurium (Kim and Slavik 1994), Listeria monocytogenes (Capita et al 2003), poliovirus (Lukasik et al 2003), and the yeast Yarrowia lipolytica (Ismail et al 2001). Trisodium phosphate has been reported in use at low to relatively high concentrations up to 12%.…”
Section: Introductionmentioning
confidence: 99%